Nutritional status and airflow obstruction: two independent contributors to CO diffusing capacity impairment in COPD - S. Baldi; G.D. Pinna; P. Crotti; S. Montemartini; E. Dacosto; F. Fanfulla; C. Fracchia; C. Bruschi (Monaldi Archives for Chest Disease, 2005)
Background. The association between weight loss and Chronic Obstructive Pulmonary Disease (COPD) has been recognised from many years. Based on the evidence that nutritional status reflects metabolic disturbances in COPD, the relationship between body mass index (BMI), severity of airflow obstruction and CO diffusing capacity (DLCO), that is the functional hallmark of emphysema, is relevant to the management of COPD phenotypes. Methods. We reviewed 104 patients with COPD (82 males), aged 66±9 years (mean±SD). Height averaged 165±8 cm, weight 71±16 Kg, FEV1 50±18 (% of predicted), RV 169±49%, and DLCO 56±26%. Multiple linear regression was performed using BMI, FEV1 and RV, as explanatory variables for DLCO. Patients were also classified into four groups according to BMI ≤ 18.5 (low), > 18.5 and ≤ 25 (ideal), > 25 and ≤ 30 (overweight), > 30 (obese), and post-bronchodilator FEV1 < 50%. Using this categorisation, a two-factor analysis of variance, testing for interaction and main effects (BMI and FEV1) was performed as confirmatory analysis for the association between BMI (kg/m2), FEV1% and DLCO%. Results. FEV1 and BMI were significantly and independently associated to DLCO according to the equation: DLCO = -18.32 + 0.65·FEV1 + 1.59·BMI (R2 = 0.40, p<0.0001). The contribution of RV % to DLCO % was largely non-significant (p=0.16). A close relationship was found between BMI (kg/m2) and DLCO %, for all of the four BMI groups segregated by post-bronchodilator FEV1%, (p<.0001). No interaction was found between these two factors (p=0.30). Conclusion. Nutritional status as assessed by BMI contributes substantially to impairment of DLCO independently of the severity of airflow obstruction. This data confirms the association between emphysematous process and weight loss in advanced COPD, independent of the airflow obstruction severity.